2018
DOI: 10.1002/alr.22193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decongestant addition to intranasal corticosteroid for chronic rhinitis: a systematic review and meta‐analysis

Abstract: Meta-analyses did not show benefits of topical decongestants addition to INCS. Adverse events of INCS-D were comparable with INCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…These drugs are indicated for maximum 10 days and are ineffective in NAR [84]. The most recent metaanalysis by Khattiyawittayakun et al showed no benefits compared to ICS monotherapy, neither in NAR nor in PAR [93].…”
Section: Is It Recommended To Add Other Drugs To Inhaled Corticosteromentioning
confidence: 99%
“…These drugs are indicated for maximum 10 days and are ineffective in NAR [84]. The most recent metaanalysis by Khattiyawittayakun et al showed no benefits compared to ICS monotherapy, neither in NAR nor in PAR [93].…”
Section: Is It Recommended To Add Other Drugs To Inhaled Corticosteromentioning
confidence: 99%
“…This controversy extends to higher level evidence as well. A 2018 SRMA of two studies by Khattiyawittayakun et al 2198 . determined that there was no demonstrable benefit to the addition of an INDC to INCS, and an IT reduction should be recommended in AR patients refractory to first‐line therapy with INCS.…”
Section: Managementmentioning
confidence: 99%
“…Decongestants increase noradrenaline release, which activates the alpha-1 and -2 adrenergic receptors and results in vasoconstriction. 6 Nasal saline irrigation improves symptoms by clearing out allergens and mucus, thinning the nasal discharge, and promoting mucociliary clearance. Leukotriene increases vascular permeability and elicits smooth muscle contraction.…”
Section: Introductionmentioning
confidence: 99%
“…When monotherapy of primary treatment fails to control the symptoms, physicians may consider combined medical therapy for additional therapeutic effects. Decongestants increase noradrenaline release, which activates the alpha‐1 and ‐2 adrenergic receptors and results in vasoconstriction 6 . Nasal saline irrigation improves symptoms by clearing out allergens and mucus, thinning the nasal discharge, and promoting mucociliary clearance.…”
Section: Introductionmentioning
confidence: 99%